VOCATIONAL AND MANAGERIAL SKILLS TO SUPPORT SME GROWTH IN GREEN LANDSCAPES: A SYSTEMIC APPROACH - Meldi Rendra; Estananto Estananto (Telkom University, 2023)
Economies in the Tasikmalaya Residences are naturally engaged in a proactive community to shift SMEs' productivity. It is a significant shift from past business culture focused on relatively strategic commodities and markets. An essential cultural factor behind the enterprise shift has been the boosting growth to generate mixed products and more and better vocational and managerial skills. The engineering service was conducted in a multi-functional tools workshop to manufacture the raw agricultural material for the finished food product. The program to increase micro-skills in vocational and managerial quality is conducted. The result is a quality of daily accounts, industrial standards, and modern trade procedures.